Managing Neuropathic Pain in Dogs - Moore, Sarah A. (Frontiers in Veterinary Science, 2016)
Disorders of the somatosensory system such as neuropathic pain are common in people with chronic neurologic and musculoskeletal diseases, yet these conditions remain an underappreciated morbidity in our veterinary patients. This is likely because assessment of neuropathic pain in people relies heavily on self-reporting, something our veterinary patients are not able to do. The development of neuropathic pain is a complex phenomenon, and concepts related to it are frequently not addressed in the standard veterinary medical curriculum such that veterinarians may not recognize this as a potential problem in patients. The goals of this review are to discuss basic concepts in the pathophysiology of neuropathic pain, provide definitions for common clinical terms used in association with the condition, and discuss available medical treatment options for dogs with neuropathic pain. The development of neuropathic pain involves key mechanisms such as ectopic afferent nerve activity, peripheral sensitization, central sensitization, impaired inhibitory modulation, and activation of microglia. Treatments aimed at reducing neuropathic pain are targeted at one or more of these mechanisms. Several drugs are commonly used in the veterinary clinical setting to treat neuropathic pain. These include gabapentin, pregabalin, amantadine, and amitriptyline. Proposed mechanisms of action for each drug, and known pharmacokinetic profiles in dogs are discussed. Strong evidence exists in the human literature for the utility of most of these treatments, but clinical veterinary-specific literature is currently limited. Future studies should focus on objective methods to document neuropathic pain and monitor response to therapy in our veterinary patients.